Asthma Linked with Rhinosinusitis: An Extensive Review - Marianne Frieri M.D., Ph.D. (Allergy & Rhinology, 2014)
Current literature related to asthma diagnosis, epidemiology, pathogenesis, and treatment linked with rhinosinusitis is important. Asthma is very heterogeneous; new theories and treatments are emerging. It is a growing epidemic among children and adults in the United States and the severity of asthma is caused by many factors such as lack of education, poor early recognition, decreased symptom awareness, improper medications, and phenotypic changes. Genetic variation, innate immune genes, those involved in tissue remodeling and arachidonic acid metabolism, and inflammatory mediators might contribute to the pathogenesis of chronic rhinosinusitis (CRS) linked with asthma. This extensive review addresses concepts of the burden of asthma and sinusitis, altered innate immunity, adaptive immunity, asthma remodeling, the airway epithelium, the role of airway smooth muscle cells, united allergic airway, genetics, an integral part in asthma, and CRS. In addition, the role of vitamin D in both asthma and CRS in the elderly and pediatric population, various treatment options, and exhaled nitric oxide are briefly addressed.